2020
DOI: 10.1038/s41598-020-60195-z
|View full text |Cite
|
Sign up to set email alerts
|

Innate T-αβ lymphocytes as new immunological components of anti-tumoral “off-target” effects of the tyrosine kinase inhibitor dasatinib

Abstract: Kinase inhibitors hold great potential as targeted therapy against malignant cells. Among them, the tyrosine kinase inhibitor dasatinib is known for a number of clinically relevant off-target actions, attributed in part to effects on components of the immune system, especially conventional T-cells and natural killer (NK)-cells. Here, we have hypothesized that dasatinib also influences non-conventional t-αβ cell subsets known for their potential anti-tumoral properties, namely iNKT cells and the distinct new in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The CD8 + T cell response in dasatinib-mediated LGL response includes TCR-Vβ + expansion of either oligoclonal or polyclonal origin with cells resembling healthy memory CD8 + T cells [ 36 ]. Importantly, dasatinib may have an immunomodulatory role in non-conventional or innate T cells by increasing cell number, activation status and Th-1 polarization of innate αβ iNKT-cells in treated CML patients [ 37 ]. In addition, it has been reported that dasatinib increased a novel innate subset termed innate CD8 + T-cell-expressing IFNγ [ 37 ].…”
Section: Dasatinib-mediated Immunomodulatory Effects In CMLmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD8 + T cell response in dasatinib-mediated LGL response includes TCR-Vβ + expansion of either oligoclonal or polyclonal origin with cells resembling healthy memory CD8 + T cells [ 36 ]. Importantly, dasatinib may have an immunomodulatory role in non-conventional or innate T cells by increasing cell number, activation status and Th-1 polarization of innate αβ iNKT-cells in treated CML patients [ 37 ]. In addition, it has been reported that dasatinib increased a novel innate subset termed innate CD8 + T-cell-expressing IFNγ [ 37 ].…”
Section: Dasatinib-mediated Immunomodulatory Effects In CMLmentioning
confidence: 99%
“…Importantly, dasatinib may have an immunomodulatory role in non-conventional or innate T cells by increasing cell number, activation status and Th-1 polarization of innate αβ iNKT-cells in treated CML patients [ 37 ]. In addition, it has been reported that dasatinib increased a novel innate subset termed innate CD8 + T-cell-expressing IFNγ [ 37 ].…”
Section: Dasatinib-mediated Immunomodulatory Effects In CMLmentioning
confidence: 99%
“…It acts on the targets BCR-ABL, c-Kit, Src family kinases (SFKS), and PDGFR-α/β. By acting on BCR-ABL and the Src family, dasatinib inhibits the downstream PI3K signaling pathway (3,79), which may induce cardiotoxicity.…”
Section: Dasatinibmentioning
confidence: 99%
“…PKs can be classified into tyrosine kinases (TKs) and serine/threonine kinases (STKs) based on the origin of the phosphorylated hydroxyl groups ( 2 ). TKs are essential cellular signaling enzymes regulating signal transduction pathways for metabolism, transcription, differentiation, proliferation, development, migration and apoptosis ( 3 ). TKs may be divided into two major classes: transmembrane receptors linked receptor tyrosine kinases (RTKs), like the PDGF receptors, and non-receptor tyrosine kinases (NRTKs), like c-SRC and BCR-ABL ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oncogenic mutations or overexpression of TK are a hallmark of cell cycle dysregulation often related to tumorigenesis ( 5 ) in hematological malignancies ( 6 , 7 ), breast cancer ( 8 ), and non-small-cell lung cancer ( 9 ). Hence, TK inhibition (TKI) is regarded as a targeted treatment for cancer as it can selectively inhibit TK proteins and halt the proliferation and growth of tumor cells ( 3 ). At present, a variety of structurally different TKIs acting at singular or multiple targets like BCR-ABL, EGFR, VEGFR, PDGFR, KIT, and ALK, have been developed with minimal toxicities and good pharmacokinetics ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%